Formulation, In-vitro Evaluations and Skin Irritation Study of Losartan Potassium Transdermal Patches: Formulation of losartan transdermal patches - Arnab Bagchi; Biplab Kumar Dey (Iranian Journal of Pharmaceutical Sciences, 2010)
Losartan potassium is a well known orally active non-peptide angiotensin II receptor antagonist. Losartan potassium and its principle active metabolites block the vasoconstrictor and aldosterone secreting effect of angiotensin II by selectively blocking the binding of angiotensin II to AT1 receptors. The drug is reported to promote the decrease in ventricular hypertrophy, salt and water excretion and vascular smooth muscle relaxation. Present investigation was aimed at the formulation of transdermal therapeutic system of losartan potassium for effective control over hypertension since the drug shows considerable first pass metabolism when administered through oral route. Blends of hydrophobic and hydrophilic polymers like ethyl cellulose with polyvinyl pyrrolidone and ethyl cellulose with hydroxypropyl methyl cellulose were used in the formulation of the medicated films. Films were prepared using dibutyl phthalate as plasticizer with eighteen different combinations of these three polymers by solvent evaporation technique. Polyvinyl alcohol was used to prepare the backing membrane. Several physicochemical parameters like moisture content, moisture uptake, thickness, film folding endurance, tensile strength, skin irritation and surface morphology of the films were studied. For all the formulations, skin permeation of the loaded drug through albino mice skin was studied using Keshary-Chien diffusion cell. Formulations containing higher proportion of hydrophilic polymers blended with lower proportions of hydrophobic polymer were found less consistent in comparison to the patches comprised of higher proportion of hydrophobic polymer.